Análise do risco de crédito das principais instituições financeiras que atuam no Brasil em relação a fatores econômicos do país - Silva, Anderson José da (2017)
Amid the country’s economic slowdown scenario, along with a sharp growth in loan portfolio records at financial institutions that were encouraged by the government in order to promote national development, a circumstantial increase in default is observed. Therefore, a closer attention is needed on credit risk management.This research aims to verify the relationship between the country’s economic factors, mainly the Selic rate, and the performance of allowance for doubtful accounts (AFDA), the total financial institutions’ assets and its impact to the credit risk and their results. Literature review presented the concepts of credit and its risk, Basel Accords risk control requirements and recommendations, and the most expressive facts from Lula and Dilma governments’ economic policy.On the basis of these data, statements from the 30 largest institutions by assets in Brazil from 2010 to 2015 were gathered and, through multiple regression generated by Minitab software it was possible to assess the impact in provisions of the following variables: Selic rate, profitability, size of loan portfolio, and asset size. Aggregating the banks in groups with similar characteristics enabled to observe their behavior in face of the variables, that Selic rate has more influence in private banks and in those with a lower credit in total asset (an increase in Selic rate tends to generate a lower AFDA in relation to the total asset). With respect to the banks with large loan portfolio in relation to the asset, a strong action of Selic rate on provisions was observed. However, an increase in this variable also impacts the provisions increase. When public banks were analyzed, it was not possible to verify a significant influence of this rate in relation to the provisions Regarding natural log of the assets and size of loan portfolio variables in total asset, it was verified their great influence, in general, in the ration between AFDA/total loan portfolio, with greater impact on public banks, the ones with smaller loan portfolio, and those with larger asset portfolio. Profitability has an influence on the ones with larger loan portfolio and on the main private banks, once profitability increases compete for the increase in the provisions on the total of assigned. The performance diagnostic of variables on credit risk ascertain the effect of each index on the response variable, which highlights the credit policy adopted by the clusters, emphasizing the crucial points to effectively manage the risk in favor of quality in financial transactions resulting in improved performance